1983
DOI: 10.1902/jop.1983.54.12.736
|View full text |Cite
|
Sign up to set email alerts
|

Psoriasis: Palatal Manifestations and Physiologic Considerations

Abstract: The histologic and clinical criteria for psoriasis involving the palate are discussed. A review of the literature shows the present case to be the fifth well-documented one in the literature. A possible explanation for the rarity of clinical manifestations in the oral cavity is presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0
1

Year Published

1988
1988
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 18 publications
1
4
0
1
Order By: Relevance
“…Case 2 displayed multiple serpigenous areas in the hard palate, which have also been previously associated with oral psoriasis. 7,9,33 The clinical appearance of the palatal lesions in these previous studies has a clear resemblance to the lesions in our report. Histologically, Case 1 displayed changes that were somewhat psoriasiform.…”
Section: Accepted Manuscriptsupporting
confidence: 82%
“…Case 2 displayed multiple serpigenous areas in the hard palate, which have also been previously associated with oral psoriasis. 7,9,33 The clinical appearance of the palatal lesions in these previous studies has a clear resemblance to the lesions in our report. Histologically, Case 1 displayed changes that were somewhat psoriasiform.…”
Section: Accepted Manuscriptsupporting
confidence: 82%
“…The first example was published by KANERVA & HiETANEN (14). Because of this possibility it is important to be able to make a histological diagnosis of oral psoriasis without being biased by the presence of skin psoriatic lesions (2,6,10). In recent years it has been indicated that geographic tongue (GT) may be one of the possible manifestations of oral psoriasis (15,16).…”
Section: Psoriasismentioning
confidence: 99%
“…Dark-skinned persons are seldom affected and American Indians are apparently not affected at all (4). The cause of the disease is unknown, but stress and anxiety, as well as winter weather, may increase its severity (2,3). Clinically, it is characterized by the presence of papular squamous lesions, their sizes varying from a few millimeters to large plaques (3).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A causa da PS permanece desconhecida, mas mecanismos ligados à hereditariedade parecem estar fortemente envolvidos na etiopatogênese desta doença. O diagnóstico de psoríase oral é definido quando o curso clínico das lesões orais é paralelo ao das lesões cutâneas (WEATHERS et al, 1974; YO UNAI; PHELAN, 1997), quando as lesões apresentam mesmo padrão histopatológico (SKLAVOUNOU; LASKARIS, 1983), quando existe história familiar positiva para PS, e pela pesquisa de antígeno leucocitário de histocompatibilidade (HLA), especialmente os antígenos B13, B17, B37, Cw4 e Cw6 (EASTMAN; GOLDBLATT, 1983). As manifestações orais, embora raras, podem ocorrer e são representadas por lesões eritemato-descamativas, devendo ser diferenciadas com outras doenças como língua geográfica, estomatite geográfica e lesões orais da Síndrome de Reiter (MIGLIARI et al, 2004;WEATHERS et al, 1974).…”
Section: Outras Doenças Mucocutâneasunclassified